Lesbian disclosure and health care seeking in the United States: A replication study. Issue 1 (2nd January 2018) - St. Pierre, Melissa
ABSTRACT: The current study explored factors associated with lesbian disclosure to health care providers (HCPs) and engagement in preventative health behaviors by replicating and extending a Canadian path analysis study with a sample of U.S. lesbians. Both patient (education, feminism, global outness, and internalized homophobia) and HCP-related (lesbian-friendly HCPs and patient comfort) factors were either directly or indirectly associated with disclosure and engagement in preventative health behaviors, including avoidance of health-compromising behaviors (e.g., smoking) and health care seeking. Importantly, findings suggest that HCPs—particularly those who are inclusive of lesbian patients—may play a role in assuaging their patients' experiences of minority stress. Overall, the findings were similar to those originally reported in the Canadian study, with the exception of internalized homophobia playing a more visible role in the current study.